Family farms of North America - John Ikerd (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
Historically, family farms held positions of respect and high esteem in the dominant cultures of North America and in much of the rest of the world. The first family farmers in North America were the indigenous peoples who had lived on the continent for centuries before the arrival of Europeans. Most depended primarily on hunting and gathering, but farming was common among many of the tribes of North America. These indigenous family farmers, like the early family farmers of Europe, usually included extended families. The families agreed on informal divisions of labour and divided the resulting production among kin groups within larger communities that farmed particular areas (Albritton 2012). An extended family might tend a specific land area, giving it some sense of ownership or rights; however, there was no real sense of private property. Most farming areas were considered 'common property' where all families could graze animals or farm cooperatively. [...]
Keywords: 330; family farms; North America